Pengembangan Model Literasi Digital dalam Pembelajaran Kitab Kuning di Ma’had Al-Jamiah UIN Maulana Mallik Ibrahim Malang - Muhammad Yasin Fatchul Barry; Sri Harini; Ahmad Lubab (Edukasia Islamika : Jurnal Pendidikan Islam, 2019)
This study aims to describe the pattern of digital literacy development among students of ma’had al-jamiah UIN Maulana Malik Ibrahim Malang. Moreover, it also describes the effectiveness of digital kitab kuning (classic books) used in the learning process. Development of digital literacy is needed not only in formal education, but also for non-formal education such as pesantren. It uses Research and Development method modified by Borg and Gall. It belongs to experimental Research conducted to find out the effectiveness of the product. The result shows an exposure to digital literacy developed in ma'had as well as the use of digital kitab kuning through an android application affected on increasing students’ ability in studying kitab kuning.